Serum mercury concentration and the risk of ischemic stroke: The REasons for Geographic and Racial Differences in Stroke Trace Element Study. (August 2018) - Chen, Cheng; Xun, Pengcheng; McClure, Leslie A.; Brockman, John; MacDonald, Leslie; Cushman, Mary; Cai, Jianwen; Kamendulis, Lisa; Mackey, Jason; He, Ka
Abstract: Background: Although biologically plausible, epidemiological evidence linking exposure to methylmercury with increased risk of ischemic stroke is limited. The effects of methylmercury may be modified by selenium, which is an anti-oxidant that often co-exists with mercury in fish. Objectives: To examine the association between serum mercury levels with the incidence of ischemic stroke and to explore the possible effect modifications by serum selenium levels and demographic and geographic factors. Methods: A case-cohort study was designed nested in the REasons for Geographic and Racial Differences in Stroke cohort, including 662 adjudicated incident cases of ischemic stroke and 2494 participants in a randomly selected sub-cohort. Serum mercury was measured using samples collected at recruitment. Multivariable-adjusted hazard ratios (HRs) and the corresponding 95% confidence intervals (CIs) were estimated using the Barlow-weighting method for the Cox proportional hazards regression model. Results: No statistically significant association was observed between serum mercury concentration and the incidence of ischemic stroke (the highest vs. lowest quintile of mercury levels: HR = 0.82; 95% CI = 0.55–1.22; P for linear trend = 0.42). Sex ( P for interaction = 0.06), but not serum selenium levels, modified the association; a more evident trend toward lower incidence of ischemic stroke with higher mercury levels was observed among women. Conclusion: This study does not support an association between mercury and the incidence of ischemic stroke within a population with low-to-moderate level of exposure. Further studies are needed to explore the possibility of mercury-induced ischemic stroke toxicity in other populations at higher exposure levels. Highlights: Serum mercury is not associated with an increased incidence of ischemic stroke. Serum selenium level did not modify the association. A more evident trend of inverse association was observed in women, but not in men.